Transcriptome sequencing and screening of anthocyanin related genes in purple potato tubers (Solanum tuberosum L.) - Xiaojuan Wu; Yanhong Ma; Peijie Wang; Juan Wu; Nan Li; Zhicheng Zhang; Rui Xie; Dan Wang; Hushuai Nie (BMC Genomics)
Abstract Background Pigmented potatoes (Solanum tuberosum L.) are rich in anthocyanin, which have antioxidantiy and play an important role in health and medical. Nevertheless, the regulation mechanism of anthocyanins in purple potato at different growth stages remain unclear. Results In this study, through using the high-throughput sequencing and systematic bioinformatics analysis, a total of 7,176 significantly different expressed genes (DEGs) were discovered from the purple potato Huasong 66 tubers at different developmental stages. Through GO and KEGG enrichment analysis, it was found that, 43 DEGs were mainly enriched in phenylpropanoid biosynthesis, flavonoid biosynthesis, and phenylalanine metabolism, which biological processes are closely related to anthocyanin biosynthesis. The quantitative RT-PCR were verified the reliability of transcriptome data. We demonstrated that DEGs or transcription factors (TFs) which related to flavonoid metabolism were involved in the anthocyanins biosynthesis, such as the protein-coding genes PAL, CHS, CHI, 4CL, F3H, UFGT, LAR, and the TFs MYB, bHLH, and HY5. Conclusion The key genes involved in anthocyanin synthesis in potato tubers were identificated, it provides new insights for molecular breeding new cultivars. These results are valuable for improving the anthocyanin in potato.